2012
DOI: 10.1242/jeb.072009
|View full text |Cite
|
Sign up to set email alerts
|

Light and vision in the deep-sea benthos: I. Bioluminescence at 500–1000 m depth in the Bahamian Islands

Abstract: SUMMARYBioluminescence is common and well studied in mesopelagic species. However, the extent of bioluminescence in benthic sites of similar depths is far less studied, although the relatively large eyes of benthic fish, crustaceans and cephalopods at bathyal depths suggest the presence of significant biogenic light. Using the Johnson-Sea-Link submersible, we collected numerous species of cnidarians, echinoderms, crustaceans, cephalopods and sponges, as well as one annelid from three sites in the northern Baha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…A more likely light source may be bioluminescence. Recent studies have observed deep-sea plankton generating light from frequent collisions with physical or biological structures on the seafloor, suggesting greater frequency of bioluminescence than in the upper water column (Craig et al 2011;Johnsen et al 2012). In this case the bending behaviour would be helpful in orienting the anemone towards the source of bioluminescence.…”
Section: Light and Feeding In Cribrinopsis Japonicamentioning
confidence: 99%
“…A more likely light source may be bioluminescence. Recent studies have observed deep-sea plankton generating light from frequent collisions with physical or biological structures on the seafloor, suggesting greater frequency of bioluminescence than in the upper water column (Craig et al 2011;Johnsen et al 2012). In this case the bending behaviour would be helpful in orienting the anemone towards the source of bioluminescence.…”
Section: Light and Feeding In Cribrinopsis Japonicamentioning
confidence: 99%
“…Although the number of benthic bioluminescent species is relatively rare in the location occupied by many of the crustaceans in this study (Johnsen et al, 2012), evidence suggesting that at least two species of deep-sea anomuran crabs possess both UV-and bluesensitive visual pigments indicates that bioluminescence still may have been a driving force behind their visual adaptations. Further studies are needed to determine whether UV sensitivity is common in the deep-sea Chirostyloidea, the superfamily to which E. picta and G. spinifer belong, as well as other deep-sea 'stalk sitters'.…”
Section: Temporal Resolution and Photosensitivitymentioning
confidence: 64%
“… max of 473.8±2.9nm for medusae (N34), 486.1±1.6nm for ctenophores (N41), and two modes for siphonophores, centered at 450.5±1.3nm (N16) and 486±2.3nm (N9) (Haddock and Case, 1999). Lophelia pertusa is not bioluminescent (Johnsen et al, 2012), but would still provide a raised substrate for the plankton to impact against, and a dual visual pigment system may help enhance contrast between the bioluminescence and the remaining bluish downwelling light as well.…”
Section: Spectral Sensitivitymentioning
confidence: 97%
See 1 more Smart Citation
“…For many deep-sea organisms, this remarkable capability was discovered for the first time by our labs when examining the live-caught specimens. For example, we have documented bioluminescence for the first time in polychaetes (Swima, Osborn et al, 2009;Chaetopterus pugaporcinus, Osborn et al, 2007;Poeobius, Haddock et al, 2010;Francis et al, 2016b), doliolids (Paradoliopsis, Pseudusa, Doliolula; Haddock et al, 2010), chaetognaths (Caecosagitta macrocephala and Eukrohnia fowleri, Haddock and Case, 1994;Thuesen et al, 2010), gastropods (two yet undescribed species), and sea anemones (Hormathiidae, Haddock et al, 2010;Johnsen et al, 2012). Bioluminescence was not known to occur in four of these taxonomic lineages before our observations.…”
Section: Lights In the Deepmentioning
confidence: 98%